The responses of SST annual cycle in the eastern equatorial Pacific to global warming - Chen, Ying-Ying; Yu, Kai (Frontiers in Marine Science, 2022)
The responses of the equatorial Pacific sea surface temperature annual cycle (SSTAC) to CO2-induced global warming are examined using 15 Coupled Model Intercomparison Project Phase 5 (CMIP5) experiments. The annual cycle patterns of global-warming simulations over 2006-2100 are compared with that of present-day simulations over 1850-2005. We see no statistically significant changes in SSTAC amplitude in the future. A coupled dynamical diagnostic framework is adopted to assess four factors, including the damping rate, phase speed and strength of the annual and semi-annual harmonic forcing of SSTAC. Under global warming, changes relative to the present-day simulations in these four diagnostic factors have a clear multi-model trend. Most coupled models exhibit relatively weaker (an average of 18%) propagation speed, and stronger annual (18%) and semi-annual (39%) external forcing. Half of the models show a relatively stronger (about one time) damping rate, while the rest show a weaker (30%) damping rate. When these four diagnostic factors are further condensed into a dynamical response factor and a forcing factor, it is revealed that the same annual cycle amplitudes with respect to the present-day simulations may result from the compensations in terms of bias in the dynamical response factor and forcing factor under increased CO2-induced warm climate.